Ability of commercial Beauveria bassiana to suppress the brown planthopper attack by inducing resistance into different rice variety - ANTONI LISWANDI; MY SYAHRAWATI; HASMIANDY HAMID; ARNETI ARNETI; JAMES RINALDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Liswandi A, Syahrawati M, Hamid H, Arneti, Rinaldi J. 2023. Ability of commercial Beauveria bassiana to suppress the brown planthopper attack by inducing resistance into different rice variety. Biodiversitas 24: 6704-6710. Beauveria bassiana (Bb) is one of the biological agents for controlling the Brown Planthopper (BPH), Nilaparvata lugens, which is generally applied directly to BPH. Nowadays, it is also used to induce resistance in rice plants; this ability has never been tested on commercial B. bassiana. The research aimed to study the effect of different rice varieties and induced resistance of commercial Bb on BPH and rice plants. The study used a Factorial Completely Randomized Design (FCRD). The first factor was the difference in rice varieties (IR 42, Cisokan, Batang Piaman), and the second factor was the soaking of the seeds and roots by commercial Bb (with commercial Bb, without commercial Bb). The results showed no interaction between rice variety and commercial Bb against BPH and rice plants. Commercial Bb reduced the attack intensity of BPH (13.31%); meanwhile, different rice varieties influenced BPH mortality, colonization, and plant growth. The Cisokan variety was better at suppressing the BPH population (45%) and suitable for colonization by commercial Bb. The IR 42 variety was more responsive than other varieties in accepting the presence of commercial Bb (16%).